Accessibility and trust: the two dimensions of consumers perception on sustainable purchase intention - Carvalho, B.; Salgueiro, M. F.; Rita, P. (International Journal of Sustainable Development and World Ecology, 2016)
The aim of this article is to shed new light on which dimensions compose sustainable purchase intention (SPI) with the purpose of understanding what moves consumers to a potentially more sustainable behaviour. Even though several studies have researched which factors influence consumer’s intention to buy in a more sustainable way, no comparable research in consumer behaviour was found studying these dimensions in a triple bottom line perspective (profit, people, and planet) that could also provide future corporate and academic applications. Therefore, this article proposes a new construct – Consumers’ Perception on SPI, defined using the C-OAR-SE procedure and measured using exploratory and confirmatory factor analysis using two different samples. In-depth interviews and online survey to actual consumers of sustainable products were undertaken in partnership with a sustainable project using its database, guaranteeing that real consumers’ perceptions were gathered for this study. The construct is proposed with two dimensions (measured by nine items): Accessibility (including facets such as product lower pricing, availability in stores, and being sold within a convenient proximity to home) and Trust (including consumers needs such as: to get to know and trust products through understanding the labels; to have had good experiences in the past or simply to have new trial opportunities). Theoretical and practical implications of the findings are also discussed.